Characterization of tumor infiltrating NK cells (TINK) and type 1 innate lymphoid cells (ILC1) in breast cancer - Santilli, Maria Cecilia (2021)
ILC1 and NK cells share several phenotypic and functional characteristics and display plasticity because they can interconvert one into another in a context-dependent manner. Indeed, TGF-β-driven conversion of TINK into intermediate populations of ILC1 (intILC1) and ILC1 has been proposed as a tumor immune escape mechanism.